Pulsatile dry cupping in patients with osteoarthritis of the knee - a randomized controlled exploratory trial - Teut Michael; Kaiser Stefan; Ortiz Miriam; Roll Stephanie; Binting Sylvia; Willich Stefan N; Brinkhaus Benno (BMC, 2012)
Abstract Introduction Cupping is used in various traditional medicine forms to relieve pain in musculoskeletal diseases. The aim of this study was to investigate the effectiveness of cupping in relieving the symptoms of knee osteoarthritis (OA). Methods In a two-group, randomized controlled exploratory pilot study patients with a clinically and radiological confirmed knee OA (Kellgren-Lawrence Grading Scale: 2-4) and a pain intensity > 40 mm on a 100 mm visual analogue scale (VAS) were included. 40 Patients were randomized to either 8 sessions of pulsatile dry cupping within 4 weeks or no intervention (control). Paracetamol was allowed on demand for both groups. Outcomes were the Western Ontario and McMaster Universities Osteoarthritis (WOMAC) score, the pain intensity on a VAS (0 mm = no pain to 100 mm = maximum intensity) and Quality of Life (SF-36) 4 and 12 weeks after randomization. Use of Paracetamol was documented within the 4-week treatment period. Analyses were performed by analysis of covariance adjusting for the baseline value for each outcome. Results 21 patients were allocated to the cupping group (5 male; mean age 68 ± SD 7.2) and 19 to the control group (8 male; 69 ± 6.8). After 4 weeks the WOMAC global score improved significantly more in the cupping group with a mean of 27.7 (95% confidence interval 22.1; 33.3) compared to 42.2 (36.3; 48.1) in the control group (p = 0.001). After 12 weeks the WOMAC global score were still significantly different in favor for cupping (31.0 (24.9; 37.2) vs. 40.8 (34.4; 47.3) p = 0.032), however the WOMAC subscores for pain and stiffness were not significant anymore. Significantly better outcomes in the cupping group were also observed for pain intensity on VAS and for the SF-36 Physical Component Scale compared to the control group after 4 and 12 weeks. No significant difference was observed for the SF-36 Mental Component Scale and the total number of consumed Paracetamol tablets between both groups (mean 9.1, SD ± 20.0 vs. 11.5 ± 15.9). Conclusion In this exploratory study dry cupping with a pulsatile cupping device relieved symptoms of knee OA compared to no intervention. Further studies comparing cupping with active treatments are needed. Trial registration Clinicaltrials.gov Identifier: NCT01057043